111k views
0 votes
Need answered ASAP!! An arithmetic sequence has this recursive formula:

(a = 6
1er = 2n-1-3
What is the explicit formula for this sequence?
A. an = (-3) + (n - 1)6
B. an = (-1) + (n -6)(-3)
C. an = 6 + (n-3)(-1)
N
D. an = 6 + (n - 1)(-3)

Need answered ASAP!! An arithmetic sequence has this recursive formula: (a = 6 1er-example-1
User Rekam
by
5.9k points

1 Answer

1 vote
Option (D) staring with the first #, then out attention where is the small N and it’s in the # 1 SO ANSWER IS THE LAST ONE -D
User Aumanjoa
by
5.6k points